Nursing Care of An Orthodox Patient with Post-Traumatic Stress Disorder and Leg Ulcers - A Case Study - Wojda, Piotr (Nursing Case Insight Journal, 2025)
Taking care of patients from a different cultural background is a challenge for health care workers. Post-traumatic stress disorder (PTSD) is known in all cultures, but behavioral symptoms may vary depending on the patient's cultural context. This study aims to answer whether adapting nursing interventions to the cultural expectations of a patient impacts the acceptance of offered nursing care and the improvement of the condition of a patient from a different cultural background. The study uses a case study of a female patient of Ukrainian origin. After collecting data through narrative interviews, indirect and direct observation, nursing diagnoses were made and nursing interventions were undertaken, adapting them to the cultural needs of the patient. Providing nursing care and adapting it to the patient's culture has a positive impact on the therapeutic relationship and treatment outcomes, and the course of nursing care. The patient's cultural origin significantly determined the course of PTSD treatment. Flexible adjustment of medical care to the patient's cultural expectations resulted in increased trust in staff, better cooperation, and improved mental state of the patient.